Commentary of landslide disaster along Ho Chi Minh road from Quang Binh to Thua Thien - Thiên, Đỗ Quang; Lý, Nguyễn Đức (Vietnam Journal of Earth Sciences, 2014)
In the past decades, there is increasing important projects on hydroelectric power, irrigation structures, transportation, mineral exploitation developed in clipping mountainous area in Binh Tri Thien provinces. On slopes, especially of Ho Chi Minh road, in the rainy season, due to heavy rain to downpour, the disaster of landslide occurs in a large scale and last in many days. Besides, most of landslides raised at man made slopes of construction. In another words, the landslide on slopes are caused by double acting from heavy rain lasting with high intensity and the rapid development of technological infrastructure on energy, industry, transportation, etc. Therefore, in this article, the authors wanted to clarify the decisive direct cause of landslide hazards on the artificial slopes along the study route.